Approximation Method for Fixed Points of Nonlinear Mapping and Variational Inequalities with Application: Kanyarat Cheawchan, Atid Kangtunyakarn - Team, Support (Thai Journal of Mathematics, 2015)
In this paper, we introduce the new method of iterative scheme {x_n} for finding a common element of the set of fixed points of a quasi-nonexpansive mapping and the set of solutions of a modified system of variational inequalities without demiclose condition and T_ω:= (1-ω)I+ω T, when T is a quasi-nonexpansive mapping and ω (0,12) in a framework of Hilbert space. Using our main result, we obtain strong convergence theorems involving a finite family of nonspreading mapping and another corollary.